Infection or Malignancy? Malignant Pulmonary Mass Mimicking Pneumonia - BOSTANCI, KORKUT (THIEME MEDICAL PUBL INC, 2016)
A 36-year-old woman, unresponsive to pneumonia antibiotherapy followed by antituberculosis treatment, was referred to our clinic. Thorax computed tomography (CT) and positron emission tomography CT showed cystic mass and mediastinal lymph node with suspicion of malignancy. Fine needle aspiration biopsy and mediastinoscopy showed no malignancy, so the patient underwent an exploratory thoracotomy. A frozen section of wedge-resected mass was reported as adenocarcinoma, leading to right lower lobectomy with mediastinal lymph node dissection. Besides cutting-edge diagnostic techniques, exploratory thoracotomy for cavitary lung lesions can still be necessary, as the last-line choice. The probability of malignancy must always be considered, despite a patient's age or symptoms.
Keywords: exploratory thoracotomy; lung cancer; positron emission tomography; pulmonary cavity